Disrupted Junctional Membrane Complexes and Hyperactive Ryanodine Receptors Following Acute Junctophilin Knockdown in Mice - van Oort, Ralph J. (2011)
BACKGROUND: Excitation-contraction coupling in striated muscle requires proper communication of plasmalemmal voltage-activated Ca(2+) channels and Ca(2+) release channels on sarcoplasmic reticulum (SR) within junctional membrane complexes (JMCs). Whereas previous studies revealed a loss of JMCs and embryonic lethality in germ-line junctophilin-2 (JPH2) knockout mice, it has remained unclear whether JPH2 plays an essential role in JMC formation and the Ca(2+)-induced Ca(2+) release process in the heart. Our recent work demonstrated loss-of-function mutations in JPH2 in patients with hypertrophic cardiomyopathy. METHODS AND RESULTS: To elucidate the role of JPH2 in the heart, we developed a novel approach to conditionally reduce JPH2 protein levels using RNA interference. Cardiac-specific JPH2 knockdown resulted in impaired cardiac contractility, which caused heart failure and increased mortality. JPH2 deficiency resulted in loss of excitation-contraction coupling gain, precipitated by a reduction in the number of JMCs and increased variability in the plasmalemma-SR distance. CONCLUSIONS: Loss of JPH2 had profound effects on Ca(2+) release channel inactivation, suggesting a novel functional role for JPH2 in regulating intracellular Ca(2+) release channels in cardiac myocytes. Thus, our novel approach of cardiac-specific shRNA-mediated knockdown of junctophilin-2 has uncovered a critical role for junctophilin in intracellular Ca(2+) release in the heart.